State-Dependent Modulation of Slow Wave Motifs towards Awakening - Shimaoka, Daisuke; Song, Chenchen; Knöpfel, Thomas (Frontiers in Cellular Neuroscience, 2017)
Slow cortical waves that propagate across the cerebral cortex forming large-scale spatiotemporal propagation patterns are a hallmark of non-REM sleep and anaesthesia, but also occur during resting wakefulness. To investigate how the spatial temporal properties of slow waves change with the depth of anaesthetic, we optically imaged population voltage transients generated by mouse layer 2/3 pyramidal neurons across one or two cortical hemispheres dorsally with a genetically encoded voltage indicator. From deep barbiturate anaesthesia to light barbiturate sedation, depolarizing wave events recruiting at least 50% of the imaged cortical area consistently appeared as a conserved repertoire of distinct wave motifs. Toward awakening, the incidence of individual motifs changed systematically (the motif propagating from visual to motor areas increased while that from somatosensory to visual areas decreased) and both local and global cortical dynamics accelerated. These findings highlight that functional endogenous interactions between distant cortical areas are not only constrained by anatomical connectivity, but can also be modulated by the brain state.